Impact of Colonoscopy Bowel Preparation on Intestinal Microbiota - O’Brien, Claire L.; Allison, Gwen E.; Grimpen, Florian; Pavli, Paul (PloS one, 2013)
The gut microbiota is important in maintaining human health, but numerous factors have the potential to alter its composition. Our aim was to examine the impact of a standard bowel preparation on the intestinal microbiota using two different techniques. Fifteen subjects undergoing colonoscopy consumed a bowel preparation comprised of 10 mg bisacodyl and 2 L polyethylene glycol. The microbiota of stool samples, collected one month before, one week before (pre-colonoscopy), and one week, one month, and three to six months after colonoscopy (post-colonoscopy) was evaluated. Two samples were taken three to six months apart from five healthy subjects who did not undergo colonoscopy. Universal primers targeting the V2-V3 region of the 16S rRNA gene were used to PCR amplify all samples for denaturing gradient gel electrophoresis (PCR-DGGE). Pre- and post-colonoscopy samples were compared using Dice's similarity coefficients. Three samples from ten subjects who underwent colonoscopy, and both samples from the five subjects who didn't, were used for high-throughput sequencing of the V1-V3 region of the 16S rRNA gene. Samples were curated and analysed in Mothur. Results of the DGGE analyses show that the fecal microbiota of a small number of subjects had short-term changes. High-throughput sequencing results indicated that the variation between the samples of subjects who underwent colonoscopy was no greater than the variation observed between samples from subjects who did not. We conclude that bowel preparation does not have a lasting effect on the composition of the intestinal microbiota for the majority of subjects.